Sphaeroplea soleirolii (Duby) Montagne ex Kütz. (Chlorophyta) – the first record for Ukraine - Burova, O.V.; Gromakova, A.B.; Zhezhera, M.D. (M.G. Kholodny Institute of Botany, NAS of Ukraine, 2024)
The paper discusses the data regarding the first discovery of Sphaeroplea soleirolii within the territory of Ukraine. The identified species falls under the genus Sphaeroplea, family Sphaeropleaceae, order Sphaeropleales, class Chlorophyceae, and division Chlorophyta. The distinctive characteristics of algae within this genus encompass the cell wall ornamentation of mature oospores, spore size and shape, and to a lesser extent, variations in the morphology of vegetative cells, including cell dimensions, chloroplast structure, and transverse partitions. Representatives of the genus Sphaeroplea are typically found in shallow ephemeral freshwater (occasionally brackish) reservoirs characterized by extended periods of drying out. As per contemporary understanding, the genus comprises 11 species (with 18 intraspecific taxa), of which only two (S. annulina and S. wilmanii) have been documented in Ukraine based on literature. S. soleirolii was first observed in Ukraine during the spring of 2023 on a temporarily flooded area in the city of Zmiiv (Chuguiv District, Kharkiv Region). The paper provides a morphological description of the identified specimens, accompanied by original photomicrographs. Additionally, comprehensive information on the global distribution of the species is presented.